Parkinson’s Disease Classification Using Inertial Signals from Smartwatches and Tree-Based Classifiers - Lobo, Pedro L. S.; Chagas, Ana Luísa de Bastos; Bucci, Giordana de Farias F. B.; Salvini, Rogerio L.; Soares, Fabrizzio A.; Felix, Juliana P. (Anais da Escola Regional de Informática de Goiás (ERI-GO), 2025)
This study evaluates the use of statistical features extracted from inertial signals obtained from smartwatches to assist in distinguishing patients with Parkinson’s disease, differential diagnoses, and healthy controls. Using a public dataset comprising data from 469 individuals, tree-based classifiers were applied. The results indicate that simple motion information can support the diagnosis of Parkinson’s disease in a non-invasive and accessible manner.